Usinabilidade do aço de corte fácil baixo carbono ao chumbo ABNT 12L14 - Costa, Ivanilson Sousa da (2014)
The purpose of this dissertation was to evaluate the machinability of low carbon free-machining leaded steel ABNT 12L14 in terms of machining force, cutting temperature, surface roughness, chip characterization, analysis of tool-chip interface and mechanical properties of materials. For this, external cylindrical dry turning trials using cemented carbide tools were conducted. To comparison of results, the free-machining of steel resulphurated ABNT 1214 was also machined. The results show that the two materials had similar mechanical properties. Machining forces and surface roughness, in the conditions of the experiments, were lower for ABNT 1214 grade. However, the results indicate that the optimum cutting conditions for the two materials are different. The ABNT 12L14 grade showed lower temperature in the chip-tool interface than ABNT 1214 grade. The form, color and chip thickness ratio of the chips showed better performance in machining ABNT 12L14 grade. Layers of manganese sulfide were found on face the tool when machining both materials and traces of lead on the rake face after machining ABNT 12L14 grade. Based on the machinability criteria employed in this dissertation, ABNT 12L14 grade showed better response for machining ABNT 1214 grade.